2020
DOI: 10.1029/2019jc015449
|View full text |Cite
|
Sign up to set email alerts
|

Water Mass Properties Derived From Satellite Observations in the Barents Sea

Abstract: The Barents Sea is a region of deep water formation where Atlantic Water is converted into cooler, fresher Barents Sea Water. Barents Sea Water properties exhibit variability at seasonal, interannual, and decadal timescales. This variability is transferred to Arctic Intermediate Water, which eventually contributes to the deeper branch of the Atlantic meridional overturning circulation. Variations in Barents Sea Water properties are reflected in steric height (contribution of density to sea‐level variations) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 72 publications
(174 reference statements)
0
4
0
Order By: Relevance
“…The SSH used for the barotropic current comes from the steric height (integrated density) and eustatic height (integrated mass which can be derived form bottom pressure) (Armitage et al., 2016; Barton et al., 2020). Steric height ( η st ) can be calculated as follows where g is gravitational acceleration, p 1 and p 2 are the ocean surface and bottom pressures in Pa, ρ ref ( z ) is a reference density calculated for T = 0°C and S = 35 with variable pressure: ηst=1gp2p11ρ(z)1ρref(z)dp ${\eta }_{st}=\frac{1}{g}\int \nolimits_{{p}_{2}}^{{p}_{1}}\frac{1}{\rho (z)}-\frac{1}{{\rho }_{\mathit{ref}}(z)}dp$ …”
Section: Methodsmentioning
confidence: 99%
“…The SSH used for the barotropic current comes from the steric height (integrated density) and eustatic height (integrated mass which can be derived form bottom pressure) (Armitage et al., 2016; Barton et al., 2020). Steric height ( η st ) can be calculated as follows where g is gravitational acceleration, p 1 and p 2 are the ocean surface and bottom pressures in Pa, ρ ref ( z ) is a reference density calculated for T = 0°C and S = 35 with variable pressure: ηst=1gp2p11ρ(z)1ρref(z)dp ${\eta }_{st}=\frac{1}{g}\int \nolimits_{{p}_{2}}^{{p}_{1}}\frac{1}{\rho (z)}-\frac{1}{{\rho }_{\mathit{ref}}(z)}dp$ …”
Section: Methodsmentioning
confidence: 99%
“…Clearly, strong variability in BSW properties exists but the mechanisms driving this variability remain elusive (Barton et al., 2018, 2020). It has been suggested that the 2005 apparent regime change was caused by a warming of AW but we lack the observations to resolve the ocean processes leading to the 2005 regime change or the processes at play for the formation of BSW from AW more generally (Loeng, 1991; Schauer et al., 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Interannual variability in BSW density stems from variability in both heat and freshwater content (Barton et al., 2020). In addition to variability on interannual time‐scales, observations have revealed that temperature in the Barents Sea varies on multidecadal time‐scales with periodicities of about 6, 10, 18, and 40 years (Levitus et al., 2009; Skagseth et al., 2008; Venegas & Mysak, 2000), while salinity may have periods of variability of about 5 and 10 years (Skagseth, 2008; Yashayaev & Seidov, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…With the development of remote sensing technology, satellite-retrieved SST products are widely used with wide coverage and strong real-time performance. In addition, they are mainly utilized in the studies of water mass properties [6], ocean circulation [7], tropical cyclone [8], weather prediction [9] and ocean numerical simulation [10,11]. In these research areas, the quality of satellite SST products has becoming a prerequisite influencing the scientific findings.…”
Section: Introductionmentioning
confidence: 99%